2020
DOI: 10.1080/09712119.2020.1813739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of Quillaja saponin on growth performance, nutrient digestibility, fecal gas emissions, and meat quality in finishing pigs

Abstract: We evaluated the effects of Quillaja saponin (400 mg/kg) on growth performance, nutrient digestibility, fecal gas emissions, and meat quality in pigs when used as a supplement in a finishing pig diet. In total, 80 finishing pigs [(Yorkshire × Landrace) × Duroc] with an average initial body weight of 61.53 ± 4.41 kg were used in a 61-day study. Pigs were allotted to one of two treatments according to initial body weight with 10 replicate pens per treatment and four pigs (two barrows and two gilts) per pen. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
2
6
1
Order By: Relevance
“…Likewise, Moniruzzaman et al ( 12 ) found that dietary CN reduced fecal ammonia gas content in weaned piglets. In accordance with the present study, it has been reported that dietary plant extracts can reduce ammonia gas emissions from the feces of finishing pigs ( 38 , 39 ). In contrast, Muniyappan et al ( 31 ) observed an insignificant effect of microencapsulated organic acids on the ammonia gas content in the feces of growing to finishing pigs.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, Moniruzzaman et al ( 12 ) found that dietary CN reduced fecal ammonia gas content in weaned piglets. In accordance with the present study, it has been reported that dietary plant extracts can reduce ammonia gas emissions from the feces of finishing pigs ( 38 , 39 ). In contrast, Muniyappan et al ( 31 ) observed an insignificant effect of microencapsulated organic acids on the ammonia gas content in the feces of growing to finishing pigs.…”
Section: Discussionsupporting
confidence: 93%
“…However, further experiments are needed to evaluate the effects of QS supplementation on the antioxidant status of breast muscle. On the other hand, WHC and drip loss are dependent on the content of protein in muscle [ 65 ]. The protein synthesis properties of flavonoids in the muscle have been proved by Kamboh and Zhu [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two pigs were randomly selected from each replicate pen and removed the sample of the right loin between the 10th and 11th ribs to measure meat quality. The sensory characteristics (colour, marbling and firmness score), lightness (L*) value, redness (a*) value, yellowness (b*) value, pH, water-holding capacity (WHC), longissimus muscle area (LMA), cooking loss and drip loss were measured according to the method reported by Dang and Kim (2020).…”
Section: Sample Collection and Measurementsmentioning
confidence: 99%